Sex Differences in Atrial Fibrillation: Evidence from Circulating Metabolites - Ningjing Qian; Junyan Jin; Ying Gao; Jiayi Liu; Yaping Wang (Metabolites)
Background: Significant sex differences exist in atrial fibrillation (AF). Better understanding of its underlying mechanism would help AF management. This study aimed to investigate the contribution of circulating metabolites to sex differences in AF and the association between them. Methods: A total of 108 patients with AF were enrolled. Untargeted metabolomics were performed in plasma samples of male and female patients. Correlation analysis with clinical characteristics and Mendelian randomization were used to identify sex-specific metabolites associated with AF, which was further validated in additional patients. Transcriptomics data of the left atrium were used to investigate the molecular alteration of the left atrium responding to identified sex-specific circulating metabolites. The effect of selected sex-specific metabolites on cardiomyocytes was further investigated. Results: A total of 60 annotated metabolites were found with different levels between male and female patients. Among these sex-specific metabolites, three metabolites, 7-Methylguanosine, succinic acid, and N-Undecylbenzenesulfonic acid, were positively related to the left atrial remodeling. Additionally, succinic acid was significantly associated with increased risk of AF (OR = 1.26; 95% CI: 1.13 to 1.40; p < 0.001). And, SUCLA2, the gene of succinic acid metabolism, was significantly increased in the left atrium of male patients (fold change = 1.53; p = 0.008). Treatment with succinic acid led to cardiomyocyte hypertrophy and mitochondrial dysfunction. Conclusions: This study highlights sex differences in circulating metabolites in patients with AF and identifies the associations between sex-specific metabolites and AF. succinic acid, which is much higher in male patients, contributes to the process of AF.